Near threshold angular distributions for the 2H(γ, Λ)X reaction. (30th June 2016) - Beckford, B.; Byd̆zovský, P.; Chiba, A.; Doi, D.; Fujii, T.; Fujii, Y.; Futatsukawa, K.; Gogami, T.; Hashimoto, O.; Han, Y. C.; Hirose, K.; Honda, R.; et al.
Abstract: A study of the ^2 H(γ, Λ) X reaction was performed using a tagged photon beam at the Research Center for Electron Photon Science (ELPH), Tohoku University. The photoproduced Λ was measured in the pπ^- decay channel by the upgraded Neutral Kaon Spectrometer (NKS2+). The momentum integrated differential cross section was determined as a function of the scattering angle of Λ in the laboratory frame for five energy bins. Our results indicated a peak in the cross section at angles smaller than θ^LAB_Λ = 0.96 . The experimentally obtained angular distributions were compared to isobar models, Kaon-Maid (KM) and Saclay-Lyon A (SLA), in addition to the composite Regge-plus-resonance (RPR) model. Both SLA(rK_1K_γ = -1.4 ) and RPR describe the data quite well in contrast to the KM model, which substantially under-predicted the cross section at the most forward angles. With the anticipated finalized data on Λ integrated and momentum dependent differential cross sections of ^2 H(γ, Λ) X [M. Kaneta et al., Nucl. Phys. A 914, 69 (2013)], we present our findings on the angular distributions.